"Vou abrir minha jurema" : vivências terapêuticas em Sergipe - Jesus, Aparecida Santana de (2021)
This work has as its central theme the use of Jurema in therapeutic contexts. Through this study, I sought to analyze the practices and meanings associated with Jurema in "neoxamanic rituals" in a municipality in Sergipe. According to Fernandes (apud Oliveira, 2012), neoxamanism can be understood, in general, as "non-traditional" uses and meanings around elements associated with the universe of shamanism, as a symbolic and rhetorical resource in models of contemporary spirituality, therapy, consumption and sociability. There is a long tradition of studies on neoxamanic rituals involving the socalled "power plants". Anthropological studies on Jurema, however, seem to be more strongly focused on use within African and indigenous religions. With this work, I sought to understand the practices and meanings associated with the use of Jurema in the context of urban neoxamanic rituals, taking as reference a therapeutic space located in Sergipe For this, I conducted the research in the period from 2019 to 2021, using several methodological strategies. In a first moment, I did fieldwork strictu sensu, participant observation, and had the opportunity to establish direct dialogue with some interlocutors. For this, I also used part of my experiences as a participant in this universe and the contact networks I established along my own path, as well as interactions. In the beginning of 2020, however, due to the measures recommended by the health authorities for social distancing because of the Covid19 Pandemic, I started to carry out the research using virtual media. With this, I started to conduct interviews online with some key informants, participated in the members' WhatsApp group, followed lives, videos, and other activities related to the therapeutic center. I realized that the central link of these therapeutic experiences revolves around Jurema. The members seek to overcome the daily tribulations of life through the use of this power plant. For them, the Jurema seems to bring clarity and understanding for what each one needs, but it also shows what one needs to improve, to solve.